Motivation, engagement and outcomes in curriculum development in a specialist SEND School in England. Issue 1 (1st February 2021) - Silver, Matt
Abstract : This article provides an insider account of one school's journey towards a curriculum offer which makes use of a meaningful, mastery project‐based approach. The initiative incorporates consideration of self‐determination theory to secure outcomes which are relevant to the needs of students. The account offers insights into a work in progress and illustrations of powerful interfaces between theory and practice.